The impact of the Bank of Japan's monetary policy on Japanese government bonds' low nominal yields - Tanweer Akram; Huiqing Li (Levy Economics Institute of Bard College, 2019)
Nominal yields for Japanese government bonds (JGBs) have been remarkably low for several decades. Japanese government debt ratios have continued to increase amid a protracted period of stagnant nominal GDP, low inflation, and deflationary pressures. Many analysts are puzzled by the phenomenon of JGBs' low nominal yields because Japanese government debt ratios are elevated. However, this paper shows that the Bank of Japan's (BoJ) highly accommodative monetary policy is primarily responsible for keeping JGB yields low for a protracted period. This is consistent with Keynes's view that the short-term interest rate is the key driver of the longterm interest rate. This paper also relates the BoJ's monetary policy and economic developments in Japan to the evolution of JGBs' long-term interest rates.
Keywords: E43; E50; E58; E60; G10; G12; 330; Japanese Government Bonds; Long-Term Interest Rates; Nominal Bond Yields; Monetary Policy; Bank of Japan; John Maynard Keynes